Protective Role of Fecal Microbiota Transplantation on Colitis and Colitis-Associated Colon Cancer in Mice Is Associated With Treg Cells - Wang, Zitao; Hua, Wenjie; Li, Chen; Chang, Hao; Liu, Ran; Ni, Yangyue; Sun, Hongzhi; Li, Yangyang; Wang, Xinyue; Hou, Min; Liu, Yu; Xu, Zhipeng; et al. (Frontiers in Microbiology, 2019)
Colitis-associated cancer (CAC) is the most serious outcome of inflammatory bowel disease, which has an alteration of commensal intestinal microbiota. However, the role of intestinal microbiota on CAC progression is not well understood. Fecal microbiota transplantation (FMT) was used for treating murine azoxymethane–dextran sodium sulfate (AOM-DSS) model of CAC. Composition of gut microbiota during FMT treatment was analyzed. RT-PCR and ELISA were used to detect the inflammatory factors, and immunofluorescence was applied to examine the phospho-NF-κB p65/p100 and Ki67 positive cells in the colons. In addition, flow cytometry was performed to analyze the immune cell after FMT treatment. Rehabilitation of the intestinal microbiota by FMT restored both the ratio and diversity of microbiota during CAC progression. Remarkably, a favorable morphometric outcome characterized by decreased tumor load and size was observed in CAC mice with FMT treatment. In addition, an anti-inflammatory function of FMT was demonstrated by decreasing pro-inflammatory factors but increasing anti-inflammatory factors through inhibiting canonical NF-κB activity and cellular proliferation in colons of CAC mice. The expression of CD4+CD25+Foxp3+ regulatory T cells (Tregs) was significantly increased after FMT treatment in CAC mice, but not Th1/2/17 cells. Our study aids in the understanding of CAC pathogenesis and reveals a previously unrecognized role for FMT in the treatment of CAC through restoring the intestinal microbiota and inducing regulatory T cells.